Digitale Pioniere in der ländlichen Regionalentwicklung: eine bibliometrische Analyse zu Digitalisierung und Leadership - Binder, Julia; Witting, Antje (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
While research into digitalisation in cities has grown strongly in recent years, rural areas have now also clearly shifted into the focus of attention. An important strand of research into digitalisation in rural areas can be described as agency perspectives. Current studies point to the driving, transformative force of key figures, for example social entrepreneurs, smart villagers or spatial pioneers. At heart, these studies propose that paths for collective action can be developed via key figures, thus generating ways to change established rules and norms. This paper represents a methodological contribution to this strand of research by subjecting the debate on leadership through key figures to a quantitative, bibliometric analysis, on the basis of which a heuristic is proposed in order to develop relevant research questions. Based on different strands of discourse, our results show that unequal spatial development ismanifested in an urban bias, but also demonstrate the potential of the growing research field in rural regional development.